Effects of the inflammatory mediator bradykinin on intestinal functions - Würner, Lisa Katharina; Justus Liebig University Giessen (My University, 2013)
Bradykinin is a peptide, which is responsible for inflammatory processes throughout thebody. In the intestine it is assumed to be involved in the development of diarrhea by alteringgastrointestinal motility and ion secretion. My PhD& #8208;thesis focused on these effects ofbradykinin on intestinal functions and on the question, how the different systems influencedby the kinin, i.e. enteric nervous system, motility and secretion, interact with each other.Therefore, I investigated the effect of bradykinin on rat myenteric neurons, rat intestinalmuscle and rat and human colonic epithelium by applying microelectrode arrays, Ca2+imaging, immunofluorescence analysis, isometric contraction measurements as well asstandard and real time reverse transcription PCR.Bradykinin stimulated rat myenteric neurons in a biphasic manner, which was shown on anaction potential level measured with microelectrode arrays as well as on a cytosolic Ca2+level, as demonstrated by Ca2+ imaging experiments. This effect was mediated by both the B1and the B2 receptor, with the B1 receptor being upregulated due to the cell culture. Thisupregulation was confirmed by immunocytochemistry as well as real time PCR. Thestimulation of myenteric neurons by bradykinin was based on an influx of Ca2+ from theextracellular space, since a removal of extracellular Ca2+ significantly reduced the bradykinininducedpeak in the fura& #8208;2 ratio.In the rat intestinal muscle bradykinin induced biphasic responses with a relaxation followedby a contraction. This effect exhibited a strong segment& #8208;dependency. Since the neurotoxintetrodotoxin did not alter the bradykinin& #8208;induced effect, the enteric nervous system wasmost likely not involved in the change of contractility. Tetrapentylammonium, a K+ channelblocker preferentially inhibiting Ca2+& #8208;activated K+ channels, reduced the relaxant componentof the response. In dissociated intestinal muscle cells bradykinin induced an increase of thecytosolic Ca2+ level as detected in Ca2+ imaging experiments. In native tissue bradykinin actsvia B2 receptors, whereas in vitro incubation induced the expression of B1 receptors, whichthen caused a purely contractile response after stimulation with a B1 agonist.153 SummaryImmunofluorescence analysis of the colonic wall and of dissociated intestinal muscle cells, aswell as RT& #8208;PCR confirmed this finding. The consecutive ablation of adherent layers of theintestinal wall strongly reduced the response to bradykinin in comparison to a controlstimulus, i.e carbachol, suggesting a contribution of non& #8208;muscle cells in the mediation of thisresponse.In Ussing chamber experiments with human and rat colonic tissue I demonstrated abradykinin& #8208;induced ion secretion. Measurements with rat full& #8208;thickness preparationsshowed reduced effects of bradykinin and the B2 receptor agonist on the change in shortcircuitcurrent compared to preparations devoid of the muscle layer. In the presence oftetrodotoxin, the effect of bradykinin was abolished in full& #8208;thickness preparations, whereasin preparations devoid of the muscle layer, the response was unaltered. This demonstratesthat the reduction of the bradykinin& #8208;response in full& #8208;thickness preparations is not due toinhibiting influences of the myenteric plexus, but to the muscle layer forming a diffusionbarrier for the kinin.In human mucosa biopsies bradykinin as well as the B2 agonist (but not the B1 agonist)induced an ion and mucus secretion. This response was reduced in ulcerative colitis patientscompared to control patients, showing that the bradykinin& #8208;system is most likely involved inulcerative colitis. Tetrodotoxin partially inhibited the bradykinin& #8208;effect on both the ion andthe mucus secretion, demonstrating a neuronal component of the bradykinin& #8208;response inthe human mucosal biopsies.These results demonstrate an involvement of bradykinin in the regulatory systems of theintestine, influencing the enteric nervous system, the intestinal muscle layer, as well as theion and mucus secreting epithelium, which might, especially on the basis of an interaction ofthese systems, lead to the beneficial as well as hazardous effects of the inflammatorymediator bradykinin on intestinal functions.

Bradykinin ist wichtiger Entzündungsmediator. Es wird angenommen, dass Bradykinin an der Entstehung von Durchfällen bei entzündlichen Darmerkrankungen beteiligt ist, indem es die gastrointestinale Motilität und die epitheliale Sekretion beeinflusst. In meiner PhD-Arbeit beschäftigte ich mich mit dem Einfluss dieses Kinins auf intestinale Funktionen und mit der Frage, inwiefern die unterschiedlichen durch Bradykinin beeinflussten Systeme, d.h. das enterische Nervensytem, die Motilität und die Sekretion, miteinander interagieren.Daher untersuchte ich die Wirkung von Bradykinin auf myenterische Neurone und die intestinale Muskulatur der Ratte sowie auf das Colonepithel von Ratte und Mensch. Die Ergebnisse meiner PhD-Arbeit demonstrieren multiple Angriffsorte von Bradykinin in den regulatorischen Systemen des Gastrointestinaltrakts. Das Kinin beeinflusst sowohl das enterische Nervensystem als auch die intestinale Muskelschicht und das ionen- und mukussezernierende Epithel. Vor allem in Hinblick auf eine Interaktion dieser Systeme scheint der Entzündungsmediator Bradykinin eine zentrale Rolle beim Zustandekommen von Entzündungsreaktionen an diesem Organsystem zu spielen.
Die Wirkung des Entzündungsmediators Bradykinin auf intestinale Funktionen
Keywords: ddc:630